The Labour Market in the Visegrad Group Countries – Selected Aspects - Szymańska, Agata (Olsztyn Economic Journal, 2017)
The aim of this paper is to compare selected aspects related to the labour market in the Visegrad Group countries. In particular, attention is paid to the analysis of labour force inactivity, the period of being unemployed and selected institutional arrangements related to the unemployment benefit systems. The research method is based on the analysis of statistical data and a review of institutional arrangements existing in each of the four countries. The analysis shows that there are differences related to the duration and the generosity of unemployment benefit systems. In terms of unemployment, the worst situation is to be found in Slovakia (especially, due to problems with an unemployment rate above the EU average, a high youth unemployment rate, and a significant proportion of long-term unemployed). In 2016 the shortest statutory duration of unemployment benefits was in Hungary, while the relatively least favourable benefit system seemed to exist in Poland.